Early predictors of clinical and mental outcome in tuberous sclerosis complex: A prospective study. (July 2018) - Benova, Barbora; Petrak, Borivoj; Kyncl, Martin; Jezdik, Petr; Maulisova, Alice; Jahodova, Alena; Komarek, Vladimir; Krsek, Pavel
Abstract: Aim: We aimed to identify early predictors of intractable epilepsy, intellectual disability (ID) and autism spectrum disorders (ASD) in the cohort of TSC patients initially diagnosed with cardiac rhabdomyomas (CR). Method: Over the period of twelve years we prospectively obtained clinical, neuropsychological, electrophysiological and neuroimaging data in a group of 22 TSC patients (9 females, 13 males) with the pre/perinatal diagnosis of CR, included to the study at the time of diagnosis. Afterwards, we statistically determined variables associated with ID, ASD and intractable epilepsy. Results: Development of ID was predicted by severe epilepsy (a higher number of anti-epileptic drugs used), a higher number of dysplastic lesions on MRI, and abnormal background activity on EEG ( p  < 0.05). Predictors of ASD included early developmental delay, abnormal background activity on EEG at the end of follow-up and a higher number of areas with dysplastic features on MRI ( p  < 0.05). Intractable epilepsy was associated with a higher number of areas with dysplastic features on MRI, ID and with TSC2 genotype. Conclusion: Adverse mental and clinical outcome was associated with intractable epilepsy and the severe anatomical brain involvement; therefore, our centre developed a tailored protocol for early identification of TSC patients at a higher risk of developing intractable epilepsy with its deleterious effect on cognitive outcome. Highlights: TSC patients at risk of developing ID, ASD and intractable epilepsy are identified. A tailored follow-up protocol to identify high-risk TSC patients was developed. Developmental trajectory of TSC patients strongly depends on their seizure compensation. Immediate seizure treatment is necessary to prevent adverse cognitive sequelae. Severe brain changes warrant closer follow-up, even in the absence of seizures.